PENGARUH KEJELASAN SASARAN ANGGARAN, TRANSPARANSI, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH: Studi Pada Organisasi Perangkat Daerah (OPD) Kabupaten Magetan - Rengganis Puspita Saharani; Siti Suharni (Universitas Merdeka Madiun, 2023)
The research aimed to examine the effect of clarity budget target, transparency and quality of human resources on the accountability of government institutions performance. The research was quantitative. The data collection techniques in this research used questionnaire directly to the respondents. Sampling method in this research using purposive sampling with a total of 50 respondents in 10 local government organizations in Magetan Regency. The data analysis was performed using multiple linear regressions analysis model with SPSS program 25 version for windows. The research of hypothesis showed that the independent variable clarity of budget target is 0,047, the independent variable transparency is 0,000, the independent variable quality of human resources is 0,244 and the adjusted R Square showed a value of 0,622 or 62,2%. The research result showed that clarity of budget target had a positive effect on accountability of government institutions performance, transparency had a positive effect on accountability of government institutions performance, and quality of human resources had a negative effect on accountability of government institutions performance.